2022
DOI: 10.1039/d2nj03911g
|View full text |Cite
|
Sign up to set email alerts
|

A novel 2D metal–organic framework probe: a highly sensitive and visual fluorescent sensor for Al3+, Cr3+ and Fe3+ ions

Abstract: The development of metal-organic frameworks (MOFs) based fluorescence sensors in detection of metal ions attracted significant interests. In this study, a novel 2D MOF Tb-DBA was constructed using Tb3+ and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 48 publications
(52 reference statements)
1
2
0
Order By: Relevance
“…Due to the energy mismatch between the ligand and Al 3+ , the increase of π* → π energy transfer of the ligand led to the enhanced fluorescence. 47–49 Several previous studies also reported similar phenomena and results. 50,51…”
Section: Resultssupporting
confidence: 68%
“…Due to the energy mismatch between the ligand and Al 3+ , the increase of π* → π energy transfer of the ligand led to the enhanced fluorescence. 47–49 Several previous studies also reported similar phenomena and results. 50,51…”
Section: Resultssupporting
confidence: 68%
“…15 Many fluorescent MOFs were used to detect Fe 3+ ions by fluorescence quenching due to their many advantages including ease of use, quick detection ability, high sensitivity, highly selective response, diverse pore topologies, high surface area, and easy separation. 16–28…”
Section: Introductionmentioning
confidence: 99%
“…Due to the importance of transition metal ions in biology and the environment, the design and synthesis of uorescent sensors that can effectively recognize transition metal ions has attracted great interest. [6][7][8][9][10] The pollution by metal ions is increasing today with the rapid development of modern industry, especially industrial effluents discharged into rivers and lakes, etc. The pollution caused by transition metal ions pollution is the most serious, of which Fe 3+ pollution is the most common.…”
Section: Introductionmentioning
confidence: 99%